Mobility design shaping future mobility : volume 2 Research /Kai Vöckler, Peter Eckart, Martin Knöll, Martin Lanzendorf (eds.) - Vöckler, Kai; Eckart, Peter; Lanzendorf, Martin; Knöll, Martin (2023)
Climate change, increasing resource scarcity, and rising traffic volumes are forcing us to develop new environmentally friendly and people-oriented mobility options. With the expansion of digital information systems, we will soon be able to reconfigure different modes of transport to suit our needs. These developments represent a significant challenge for designing a wide range of different mobility spaces. While Volume 1 of this series focused on practical aspects, Volume 2 collects research methods and findings from the fields of design, architecture, urban planning, geography, social sciences, traffic planning, psychology, and communication technologies. The book's consideration of the possibilities and prospects of usercentred mobility design offers an important contribution to the ongoing debate concerning the mobility revolution.